Effect modification of social-context changes on mental disability in China from 1987 to 2006: a multi-level study of 1.9 million people. (December 2017) - Wang, Zhenjie; Pang, Lihua; Li, Ning; Guo, Chao; Chen, Gong; Zheng, Xiaoying
Abstract Background Very little literature has explored how mental disability in China is connected with inequalities in social and environmental contexts. In the study described herein, we determine whether social-context inequalities were associated with mental disability in China from 1987 to 2006. Methods Data were derived from national representative population-based data from the 1987 and 2006 China National Sample Survey on Disability. Both surveys used multistage, stratified random cluster sampling, with a probability proportionate to size, to derive nationally representative samples. A multilevel logistic regression model was applied to estimate the effects of province-specific contextual characteristics on men and women. We also examined the association with mental disability risk stratified by selected covariates. Study populations were (N  = 698, 810) in 1987 and (N  = 1, 260, 947) in 2006. Result Most of the province-level variables in the 1987 and 2006 surveys were unrelated to mental disability risks in either men or women after controlling for individual characteristics. The age-adjusted prevalence of mental disability nearly doubled among men and women from 1987 to 2006. The effects of the province-specific prevalence of agricultural, forestry, animal husbandry and fishery activities and the percentage of the population age 65 and over significantly lowered the risk of mental disability among women in 1987, by 48 and 32%, respectively. Moreover, the number of health professionals modified the association with per capita gross domestic product (GDP) among women but only in 1987. Conclusion To face the challenges of mental disability and interprovincial inequality, the Chinese government should adjust its strategies not only for health-care systems but also to correct for inequalities in interprovincial development; this action may help prevent mental disability.